Diversity of soil fertility management options in maize-based farming systems in northern Benin: A quantitative survey - Tovihoudji, Pierre G.; Akpo, Firmin I.; Tassou Zakari, F.; Ollabodé, Nouroudine; Yegbemey, Rosaine N.; Yabi, Jacob A. (Frontiers in Environmental Science, 2023)
Introduction: Maize-based production systems in Sub-Saharan Africa are largely based on family farming, which is characterized by low-input, nutrient-mining agriculture and practices. These systems usually promote soil degradation through loss of organic matter and erosion. The present study characterizes farms and main soil fertility management options in maize-based farming systems of the northern Benin. Methods: The study was conducted in the municipalities of Malanville, Banikoara and Bembèrèkè. We sampled randomly and interviewed 262 maize farmers, and the statistical analysis (distribution of means and frequencies, chi-square, ANOVA, etc.) was performed. Results and discussion: The results show that maize farming characteristics and socioeconomic conditions (land use and labor, production activities and land allocation, institutional arrangements on land, access to labor and capital, etc.) were diverse across locations and exhibited a wide variation within locations. Several practices were used for the management and sustainable maintenance of soil fertility in maize production systems in northern Benin: maize-legume intercropping, cotton-maize rotation, and mineral and organic fertilizers application. Most of farmers occasionally or regularly used mineral fertilizers (95.4%), followed by legume-cereal rotation/ intercropping (51.9%). Overall, 23.6% and 58.4% of farmers consistently used mineral fertilizer over the last 5 and 10 years, respectively. The amount of applied mineral fertilizer did not significantly vary between locations with an average (applied day after sowing, DAS) of 131.7 ± 13.7 (22 ± 8 DAS), 58.7 ± 9.6 (44 ± 5 DAS) and 164.7 ± 25.4 (38 ± 11 DAS) kg ha−1 for NPK, urea and Mix NPK + urea, respectively applied at, and days after sowing. Most farmers spread the fertilizer around the plants without covering with soil particles. Manure was applied exclusively to food crops through transporting and corralling (28.2%); and most farmers also used manure from their own livestock while few farmers used cattle corralling. Farmyard manure was mainly spread (100% of respondents) on the surface before plowing at the beginning of the rainy season. Maize farmers applied mineral fertilizer based on the level of initial soil fertility (naturally fertile or poor, degree of erosion etc.) and fertilizer purchase costs. Manure was not widely used as an alternative to chemical fertilizers; therefore, farmers need more strengthening and technical assistance on the production of organic fertilizers and manure storage. The findings are useful for policymakers on encouraging the successful implementation of sustainable soil fertility management strategies of maize-based farming systems in northern Benin.